Blepharitis as an early sign of metabolic syndrome: a nationwide population-based study. Issue 9 (16th November 2017) - Lee, Chia-Yi; Chen, Hung-Chi; Lin, Hui-Wen; Huang, Jing-Yang; Chao, Shih-Chun; Yeh, Chao-Bin; Lin, Hung-Yu; Yang, Shun-Fa
Abstract : Background: To investigate the relationship between blepharitis and metabolic syndrome (MetS) by using the Longitudinal Health Insurance Database (LHID) of Taiwan. Methods: This retrospective cohort study was conducted using data collected from the LHID for the period from 2009 to 2013. This study enrolled patients who received a diagnosis of blepharitis according to the International Classification of Diseases, Ninth Revision, diagnostic code. The exclusion criteria were legal blindness, eyeball removal, ocular tumours prior to the diagnosis of blepharitis, and patients diagnosed with blepharitis and initiated antibiotic treatment concurrently. An age-matched, gender-matched and disease-matched population without blepharitis served as the control group. Multivariate analysis with a multiple Cox regression model was applied to analyse the data. Results: In this study, a total of 10 093 patients with blepharitis were included in the study group, and another 40 372 participants without blepharitis were included in the control group. Conditional logistic regression revealed a higher cumulative probability of hyperlipidaemia and coronary arterial disease. After adjustment, patients with blepharitis had a higher probability of developing new MetS than controls. According to subgroup analysis, hyperlipidaemia and coronary artery diseases were significantly correlated with the prior development of blepharitis. However, hypertension and diabetes mellitus and insulin resistance showed no correlation with blepharitis. Conclusion: Blepharitis is significantly related to MetS and can serve as an early sign of MetS. Additional studies should examine the relationship between blepharitis and MetS in terms of severity.